مؤشرات جودة الخدمات الطلابية بجامعة الملك خالد - الشهراني, محمد; ال زاهر, علي (جامعة الوادي - University of Eloued, 2022)
هدف البحث إلى تعرف مؤشرات جودة الخدمات الطلابية بجامعة الملك خالد في مجالات (خدمات شئون الطلاب، والإسكان، والتغذية، والإعانات المتنوعة، والأنشطة المختلفة، والتوجيه والإرشاد، والحقوق الطلابية)، والمتطلبات اللازمة لتطبيق مؤشرات الجودة، وتم استخدام المنهج الوصفي، والاستبانة لجمع المعلومات من عينة عشوائية (464) من طلاب المستوى السابع (بنين) في جميع كليات جامعة الملك خالد بالقريقر بأبها. وتوصل البحث إلى أن مؤشرات جودة الخدمات الطلابية بجامعة الملك خالد في مجالات (خدمات شئون الطلاب، والإسكان، والتغذية، والإعانات المتنوعة، والتوجيه والإرشاد، والأنشطة المختلفة)، تتوافر بدرجة متوسطة، بينما مؤشرات جودة الحقوق الطلابية تتوافر بدرجة قليلة، كما توصل البحث إلى موافقة أفراد عينة الدراسة على أهمية جميع المتطلبات اللازمة لتطبيق مؤشرات جودة الخدمات الطلابية. Abstract: The objective of the research is to identify the quality indicators of student services at King Khalid University in the areas of (student affairs services, housing, nutrition, various subsidies, various activities, guidance and guidance, and student rights), and the requirements for the application of quality indicators, The descriptive curriculum and the questionnaire were used to collect information from a random sample (464) of seventh-level students (boys) at all levels. The research found that the quality indicators of student services at King Khalid University in the areas of (student affairs services, housing, nutrition, various subsidies, guidance and counselling and various activities) are available on an intermediate basis, while the quality indicators of student rights are available to a small degree. The research also found that the research sample members agreed on the importance of all the requirements for applying the quality indicators of student services.
مقال
Keywords: مؤشرات الجودة؛ الخدمات الطلابية؛ جامعة الملك خالد; quality indicators; Student services; King Khalid University